Imaging of shallow coal structures using 2D6C Mini-SOSIE. Issue 1 (1st December 2016) - Strong, Shaun; Alderman, James; Hearn, Steve
Abstract : At a trial field site in the Bowen Basin previous seismic surveys had difficulty imaging the coal seams near the base of weathering. It was suspected that these may be highly structured which could complicate future open-cut mining. To improve the understanding of the geology a multicomponent 2D trial was conducted. This used the Mini-SOSIE technique to simultaneously generate P-wave and transverse S-wave energy. This allowed for the processing and interpretation of three separate datasets (P, S, and PS). In this case, the PS image provided the best structural interpretation. This was achieved using information (e.g. statics and velocities) gained from processing the pure P and S datasets.